Pelatihan Desain Web untuk Menambah Pengetahuan Siswa Madrasah Tsanawiyah Al-Mukhlis Desa Jatisari Kabupaten Bandung - Ernawati, Tati; Ekawati, Nia; Iskandar, Rachmat; Tresnawati, Shandy; Raafidiani, Reni; Ihsan Kamil, Ali (ASOSIASI IDEBAHASA KEPRI, 2025)
The PkM activity aims to provide theoretical and practical training about web design that participants know and understand web design used Bootstrap. It is expected that this training will help students understand the web design concept. Partner is Pondok Pesantren Al-Mukhlis Desa Jatisari Kabupaten Bandung. The method used in PkM activities is training accompanied by demonstrations to increase the skills of participants related to web design material. PkM activities for junior high school participants have been realized in the form of training on Tuesdayy, August 31 2024. This PkM activity shows that students have acquired basic knowledge of web design. The students' active participation during the training indicates a positive response to the training material.